1980
DOI: 10.1007/bf01875966
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemical group specific reagents on sodium entry and the amiloride binding site in frog skin: Evidence for separate sites

Abstract: Previously we have shown that the inhibition of active transport by amiloride is noncompetitive with sodium in Rana catesbeiana skin, suggesting that amiloride acts at a site separate from the sodium entry site (Benos, D.J., Mandel, L.J., Balaban, R.S. 1979, J. Gen Physiol. 73:307). In the present study, the effects of a number of sulfhydryl, amino, and carboxyl group selective reagents were studied on short-circuit current (Isc) as well as the efficacy of amiloride in bullfrog skin, to determine those functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…The present data are most consistent with significant alterations of the binding sites associated with the classical Na channel rather than a fundamentally distinct channel. Work by several investigators studying electrogenic Na absorption in a variety of tight epithelia has suggested that there are specific loci associated with the Na channel that modify its behavior: an amiloride-binding site (20), a Na self-inhibition site (21,22), a sulfhydryl group sensitive to mercurial agents ( 12), a trypsin-sensitive site (23), and a methyl receptor locus (24). There may be overlap among these sites; however, it appears that the amiloride-binding and Na self-inhibition sites are distinct (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present data are most consistent with significant alterations of the binding sites associated with the classical Na channel rather than a fundamentally distinct channel. Work by several investigators studying electrogenic Na absorption in a variety of tight epithelia has suggested that there are specific loci associated with the Na channel that modify its behavior: an amiloride-binding site (20), a Na self-inhibition site (21,22), a sulfhydryl group sensitive to mercurial agents ( 12), a trypsin-sensitive site (23), and a methyl receptor locus (24). There may be overlap among these sites; however, it appears that the amiloride-binding and Na self-inhibition sites are distinct (20).…”
Section: Discussionmentioning
confidence: 99%
“…In rabbit distal colon, PCMBS "freezes" the Na conductance of the apical membrane at a mean value of 2-3 ,ueq cm-2 h-' and renders the transport amiloride-insensitive (25). Sulfhydryl reagents also stimulate electrogenic Na absorption in frog skin (12,26); however, in contrast to distal colon, this Na transport is blocked by amiloride. The response of the cecum to PCMBS and phenamil is similar to that found in frog skin rather than distal colon: i.e., sulfhydryl reagent stimulation of Na transport that retains its sensitivity to an amiloride analogue.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of agents which modify carboxyl groups have been studied by several laboratories with mixed results. Carbodiimides were found to block Na transport by the skin of Rana temporaria (Zeiske & Lindemann, 1975) but not by that of other frog species (Benos et al, 1980a) or by the toad bladder (Harms & Fanestil, 1977). EEDQ, a more amphipathic carboxyl-modifying reagent, has been shown to inhibit Na transport in toad bladder, and the action of this reagent is protected against by amiloride (Park, Kipnowski & Fanestil, 1983):…”
Section: Are Carboxyl Groups Involved In Transport Through the Channel?mentioning
confidence: 97%
“…Ag § has also been shown to increase the cation conductance of toad bladder (Walser, 1970) and rat ileum (Clarkson & O'Toole, 1964). Similarly, pCMBS has been shown to increase the cation conductance of total urinary bladder (Spooner & Edelman, 1976) and to stimulate short-circuit current (and by inference Na + transport) across frog skin (Benos, Mandel & Simon, 1980). In addition to the Hg2+-induced increase in cell membrane K § permeability, we also observed a delayed inhibition of both ouabain-sensitive and nystatin-stimulated QO2.…”
Section: Discussionmentioning
confidence: 63%